Island Health Crisis: Bridging Gaps in Indonesia's Healthcare Deserts - Mangoma, Joyce; Sulistiadi, Wahyu (UI Scholars Hub, 2024)
This narrative literature review examines critical healthcare challenges in Indonesia's island communities, focusing on workforce shortages, inadequate health infrastructure, and the profound impact of geographical and socioeconomic factors. Drawing from eight studies published between January 2000 and December 2023, the discussion highlights both the strengths and weaknesses of existing research. The studies were selected based on their relevance to healthcare issues in island communities, rigorous methodological approaches, and significant insights into healthcare challenges and solutions. This time frame was chosen to encompass a comprehensive evolution of healthcare challenges and responses, particularly considering the effects of the COVID-19 pandemic. Grounded in the Diffusion of Innovations and Health Belief Model frameworks, the study proposes evidence-based strategies to enhance healthcare accessibility and quality in these underserved regions. The Health Belief Model is employed to understand health behaviors within island communities, addressing perceived susceptibility, severity, benefits, and barriers. Strategies include increasing awareness of health risks, highlighting the benefits of telemedicine and improved infrastructure, and reducing access barriers through incentives and infrastructural enhancements. In contrast to, The Diffusion of Innovations Theory guides the dissemination of new healthcare practices and technologies. Emphasizing innovation attributes such as relative advantage, simplicity, trialability, and observability, and utilizing effective communication channels and local social systems. The study aims to promote the adoption of telemedicine and other innovations. By engaging community leaders and health workers, and considering the time needed for adoption, the proposed recommendations aim to accelerate the diffusion process, ultimately improving healthcare accessibility and outcomes in Indonesia's island communities.